The Analgesic Effect of Extracts and Fractions of Sanchezia nobilis Hook.f. Leaves - Xuan, Bui Thi; Duc Loi, Vu; Minh Ngoc, Tran; Duc Canh, Vu; Bich Thuy, Tran (VNU Journal of Science: Medical and Pharmaceutical Sciences, 2018)
Abstract: Evaluation of central analgesic efficacy with two experimental models was the hot-plate method and white needle-guided method for the n-hexane extract and ethyl acetate fraction of Sanchezia nobilis Hook.f. leaves collected in Nam Dinh province. The study results show that by oral administration, at a dose of 64 mg/kg/day, 192 mg/kg/day for n-hexane and 16 mg/kg/day, 48 mg/kg/day for ethyl acetate fraction, for 7 consecutive days, the ethyl acetate fraction had more pronounced central analgesic effect than the n-hexane fraction. Keywords: Sanchezia nobilis Hook.f., central analgesic effect , hot-plate method, needle-guided method.  References [1] Nguyễn Tiến Bân, Danh mục các loài thực vật Việt Nam. Nhà xuất bản Nông nghiệp, 2005, Tập 3. [2] Leonard, E.C.S., Sanchezia and related American Acanthaceae. Rhodora, 1964. 66: p. 313-343. [3] Abu.Shuaib al et., Preliminary phytochemical screening and cytotoxic potentials from leaves of Sanchezia speciosa Hook. f. International Journal of Advances in Scientific Research, 2015. 1(3): p. 145-150. [4] Mohammadjavad Payda al et, In vitro anti-oxidant and anti-cancer activity of methanolic extract from Sanchezia speciosa leaves. Pakistan Journal of Biological Sciences, 2013. 16: p. 1212. [5] Vogel HG, Chapter H: Analgesic, Anti-Inflammatory, and Anti-Pyretic Activity, Drug Discovery and Evaluation: Pharmacological Assays. 3rd edition, Springer, 2008: p. 670-773. [6] Mishra D, Ghosh G, Kumar PS and Panda PK,An experimental study of analgesic activity of selective COX-2 inhibitor with conventional NSAIDs. Asian Journal of Pharmaceutical and Clinical Research, 2011. 4(1): p. 78-81. [7] Funai Y, P.A., Uta D et al, Systemic dexmedetomidine augments inhibitory synaptic transmission in the superficial dorsal horn through activation of descending noradrenergic control: an in vivo patch-clamp analysis of analgesic mechanisms. Pain, 2014. 155(3): p. 617–628.